Requirement and Evaluation Analysis on Application Performance Partnership Inventory and Reporting (Pevita) Version 2 Telkom Indonesia Based on Prototyping - Akbar, Habibullah; Eka Mira, Risviyan; Karsono, Kundang; Setijadi (International Journal of Psychosocial Rehabilitation, 2020)
PEVITA (Performance Partnership Inventory and Reporting Application) is an application used by Telkom and Telkom Group Subsidiaries / Partners to monitor and evaluate Partner Performance in the Telkom Indonesia Service Assurance (SVA) Enterprise Service Division (SVA). However, the PEVITA version 1 application still has drawbacks, namely the meeting time management menu has not been resolved and the display is unresponsive if accessed via mobile. The solution to these problems the authors suggest modeling the system using the prototyping method. Business processes are modeled using the Business Process Modeling Notation (BPMN) modeling standard version 2.0 to assist OSM, managers, officers and partners in decision making activities. Problem analysis uses the fishbone method to analyze the cause of a problem or condition in PEVITA version 2. The first stage in the prototyping method is requirements analysis using Software Requirements Specifications (SRS) requirements specifications for a software system that is a document created when a software will develop. The second stage of design uses use case diagrams, activity diagrams, Entity Relationship Diagrams, user interfaces. The third step is making mockup using marvel application. The fourth step is evaluating usability testing using the System Usability Scale (SUS) to measure perceived usefulness in applications. From the research results it can be seen that feature testing is that all features in the application can be used. System Usability Scale (SUS) of respondent's questionnaire regarding the function of the application 10 questions 10 of respondents (staff / officer / manager / OSM) get an average score of 79 SUS and 10 of partner respondents get an average score of SUS 80. With grade B level which means good. With this application, it is expected that the meeting time management menu will be added and the PEVITA version 2 application will be designed via mobile.